Cover Feature: Resolving the Chemical Formula of Nesquehonite via NMR Crystallography, DFT Computation, and Complementary Neutron Diffraction (Chem. Eur. J. 5/2023). Issue 5 (5th January 2023) - Cui, Jinlei; Prisk, Timothy R.; Olmsted, David L.; Su, Vicky; Asta, Mark; Hayes, Sophia E.
Abstract : Mg‐containing species can "chemically trap" CO2, and nesquehonite is one such metastable mineral. Its chemical formula has been debated for decades as Mg(HCO3 )(OH)⋅ 2 H2 O or MgCO3 ⋅ 3 H2 O. The thermodynamics of the route to stable carbonates require knowledge of the captured CO2 as either a carbonate or bicarbonate. To determine the precise atomic coordinates of hydrogens present, we combined solid‐state 13 C NMR lineshapes and REDOR with density functional theory and confirmation by neutron diffraction. The perturbation of 13 C NMR lineshapes by nearby hydrogens is a persuasive indicator. More information can be found in the Research Article by S. E. Hayes and co‐workers (DOI: 10.1002/chem.202203052 ).